A new species of Alapona DeLong (Hemiptera: Cicadellidae: Gyponini) from Amazonas State, Northern Brazil - Gonçalves, Clayton Corrêa; Takiya, Daniela Maeda; Mejdalani, Gabriel (Zootaxa, 2013)
Gyponini is the largest tribe of Iassinae, comprising 1,080 species in 53 genera (Freytag & Sharkey 2002, Engel & Takiya 2012). The tribe is restricted to the New World, with 75% of genera endemic to the Neotropical and 8% endemic to the Nearctic Region (Nielson & Knight 2000). Alapona DeLong (1980) is a poorly known Neotropical genus, previously known from a single species from Peru, A. elabora DeLong, 1980, described based on a single specimen. In this paper, a new species, Alapona modesta sp. nov., is described based on a single male specimen collected in Northern Brazil, which is deposited in the Instituto Nacional de Pesquisas da Amazônia (INPA), Manaus, Brazil. Considering that approximately 32% of the genera of the tribe are monotypic, we consider this a valid contribution.